Involuntary resettlement sourcebook : planning and implementation in development projects. - World Bank (Washington, DC : World Bank, 2004)
A sourcebook offering guidance on how to handle the problem of moving people in the interests of development with sensitivity and in a manner which is efficient and effective.
Includes bibliographical references and index.
oif 06/03/15
Loan
Keywords: Land settlement -- Developing countries; Migration, Internal -- Developing countries; Forced migration -- Developing countries; Economic development projects -- Developing countries; Migration, Internal -- Developing countries